The Features of the Personal Characteristics in Novels - Marupova, Aziza Axtamovna (European Journal of Life Safety and Stability (2660-9630), 2023)
this article is about the features of the personal characteristics in novels, it is important to identify extra meaning in the semantics of the term that is significant for communication, cultural and traditional knowledge, and fiction comprehension. It is essential to become acquainted with the peculiarities of the characters in a literary book in order to better grasp the storyline and emotional content of the text. The study of speech methods for creating connotative meanings that supplement descriptions of national realities, cultural customs, or properties of national character, which serve as the basis for the lexical and stylistic means used by authors and the material for revealing the artistic image, is a major focus of modern linguistics.